The Role of Advanced Polarimetric Calibration in High-Precision Pulsar Timing - Rogers, Axl Floyd (Auckland University of Technology, 2025)
This thesis explores the impact of instrumental errors in pulsar timing array (PTA) data. PTAs aim to detect low-frequency gravitational waves from a stochastic background of supermassive black hole mergers by monitoring the pulse arrival times of an array of millisecond pulsars with extreme precision. Although PTAs are making significant progress toward this goal, their measurements remain sensitive to unmodeled calibration errors. Conventional methods employed by current timing pipelines are limited in their ability to handle complex instrumental effects and polarization distortions. The primary aim of this research is to enhance the sensitivity of PTA experiments by implementing more accurate methods for instrumental calibration and pulse arrival time estimation. We employ Measurement Equation Template Matching (METM) for polarimetric calibration and Matrix Template Matching (MTM) for arrival time estimation. These techniques lead to a reduction in timing residuals and a decrease in white noise by up to sixfold in the Parkes Pulsar Timing Array data, compared to traditional Scalar Template Matching and conventional calibration based on the Ideal Feed Assumption. While both METM and MTM enhance the time-of-arrival fit, our analysis shows that METM yields only a slight reduction in the median error scale factor---defined here as the multiplicative factor (EFAC) applied to ToA uncertainties to match observed scatter in timing residuals---whereas MTM produces significant improvements. Both methods decrease the overall error added in quadrature (EQUAD). However, METM slightly increases the median uncertainty-weighted standard deviation of the whitened (red-noise-removed) post-fit timing residuals, whereas MTM markedly reduces both the median and maximum values. These results underscore MTM's effectiveness in modeling and mitigating residual calibration errors, thereby significantly enhancing arrival time precision. These findings have important implications for future PTA data releases, including improved accuracy in arrival times, better sensitivity to errors in solar system ephemerides and terrestrial time models, more precise measurements of pulsar properties, and increased sensitivity to the stochastic gravitational wave background.